Variations of Clinical Target Volume Delineation for Primary Site of Nasopharyngeal Cancer Among Five Centers in China - Zhang, Shichuan; Yang, Shuang; Xu, Peng; Xu, Yun; Zhou, Guanqun; Ou, Xiaomin; Wu, Runye; Lan, Mei; Fontanarosa, Davide; Dowling, Jason; Wang, Xiaoshen; Lin, Shaojun; et al. (Frontiers in Oncology, 2020)
Purpose: To investigate the current status of CTV delineation for primary site of nasopharyngeal cancer (NPC) among five large tertiary cancer centers in China. Materials and methods: The simulation CT and MR images of a patient with T3N2M0 NPC were sent to the centers participating. Fourteen experienced physicians contoured the targets independently and the outlined structures were compared. The consistency and differences among these 14 CTVs are discussed. Results: Two different CTV designs were used in the centers. “one-CTV” design defines one CTV with a dose of 60 Gy, whereas “two-CTV” design has a high risk CTV with dose of 60 Gy and a medium risk CTV with dose of 54 Gy. We found that the coverage of prophylactic area is very consistent between these two designs. The variances on the coverage of some sites were also significant among physicians, including covering cavernous sinus at un-involved side, posterior space of styloid process and caudal border on posterior pharyngeal wall. Conclusions: Standardization is the main requirement for personalization of care, our study shows that among the 14 physicians in the five centers the coverage of prophylactic areas is in excellent agreement. Two distinct strategies on CTV design are currently been used and multiple controversies were found, suggesting further optimization of CTV for primary site of NPC is needed.